1999
DOI: 10.1021/ma990419d
|View full text |Cite
|
Sign up to set email alerts
|

Water-Soluble Palladium(II) Catalysts for the Alternating Co- and Terpolymerization of CO and Olefins in Aqueous Phase

Abstract: The water-soluble diphosphine (NaO3S(C6H4)CH2)2C(CH2PPh2)2 (Na2DPPPDS) was employed to prepare the bis-trifluoroacetate Pd(II) complex Pd(Na2DPPPDS)(CO2CF3)2·2THF (1). The catalytic performance of 1 in the co- and terpolymerization of CO and ethene and propene in water has been studied in different experimental conditions. In combination with both a protic acid, commonly p-toluenesulfonic acid, and an organic oxidant such as 1,4-benzoquinone, 1 forms the most efficient catalyst systems ever reported for the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 43 publications
3
46
0
5
Order By: Relevance
“…For the water-soluble catalyst [Pd(CF 3 COO) 2 (Na 2 dppp-s)] 2THF/TsOH (TsOH/Pd = 20-300) it has been reported that after 3 h the catalytic activity, measured by plotting the consumption of the gaseous monomers versus time for 3 h reactions, is reduced to about 1/10 of the maximum value that is reached after ca. 30 s, even in the presence of benzoquinone (BQ/Pd = 80) [17]. The fact in the present case the activity remain almost constant after 3 h suggests that CH 3 COOH efficient by reoxidizes Pd(0) with formation of a Pd-H species which starts the catalytic cycle (see the proposed catalytic cycle of Scheme 1, equilibrium a).…”
Section: Effect Of the Reaction Conditions On The Catalyst Activitymentioning
confidence: 50%
See 3 more Smart Citations
“…For the water-soluble catalyst [Pd(CF 3 COO) 2 (Na 2 dppp-s)] 2THF/TsOH (TsOH/Pd = 20-300) it has been reported that after 3 h the catalytic activity, measured by plotting the consumption of the gaseous monomers versus time for 3 h reactions, is reduced to about 1/10 of the maximum value that is reached after ca. 30 s, even in the presence of benzoquinone (BQ/Pd = 80) [17]. The fact in the present case the activity remain almost constant after 3 h suggests that CH 3 COOH efficient by reoxidizes Pd(0) with formation of a Pd-H species which starts the catalytic cycle (see the proposed catalytic cycle of Scheme 1, equilibrium a).…”
Section: Effect Of the Reaction Conditions On The Catalyst Activitymentioning
confidence: 50%
“…Excess of acid inhibits the hydrolysis of a Pd-acyl bond as observed in water with sulphonated dppp ligands [15,20]. The overall mechanism is basically similar to the one proposed by Bianchini et al with water-soluble Pd(II) catalysts [17] (species (3) can be actually a ␤-chelate at equilibrium with an enolate isomer which undergoes protonation of the C2 carbon atom [29]). The CH 3 COOH-H 2 O reaction medium not only guarantees a sufficient solubility of the two monomers and the catalytic system but, more important, on one hand the acid stabilizes the [Pd-H] + species (equilibrium a of Scheme 1; see also the last equilibrium of reactions 1), on the other it is likely that water prevents coordination of AcO to the cationic hydride (1) [28].…”
Section: On the Proposed Catalytic Cyclementioning
confidence: 64%
See 2 more Smart Citations
“…These are mainly obtained by sulfonation of the diphosphine ligands (ca. 7 kg PK/(gPd·h) [22][23][24][25][26][27][28]), but also by fitting the phosphorus atoms with hydroxyl alkyl groups [29,30], or generally by using tenside phosphorus ligands [31].…”
Section: Introductionmentioning
confidence: 99%